Signal integrity in microelectronic hybrid systems made on metal substrates. Issue 1 (4th February 2019) - Klepacki, Dariusz; Sabat, Wieslaw; Kamuda, Kazimierz; Kurylo, Kazimierz
Abstract : Purpose: This paper aims to present the problems connected with integrity of electrical signals in microelectronic hybrid systems made on metal substrates. The systems made on ferritic and austenitic sheet substrates were selected for the analysis. Design/methodology/approach: For experimental investigations for the identification of the per-unit-length parameters for the simplest planar structures realized in thick-film technology on metal substrates, three types of path test systems with different geometric parameters were made. For the test circuits' realization, the metal substrates of ferritic stainless steel of H17 grade (1.4016) with a thickness of 1 mm were selected. The sizes of 110 × 60 mm were obtained by laser cutting which process was required to obtain sufficient flatness of the substrates. Measurements were conducted using special elaborated equipment. Findings: For selected configurations of conductive paths, the results of calculations and measurements of the range of variability of residual parameters for the systems of mutually parallel paths were presented. For selected path systems, the results of signals integrity analysis in mutually parallel path systems have been included. Originality/value: The influence of configuration of paths, their geometrical and physical parameters on the value of residual elements parameters was determined, and their role in propagation process of fast-changing signals in the mutually parallel path systems was analyzed. These effects are very important from the point of view of electromagnetic compatibility and signal integrity of electronic circuits.